Topografia rzymskiej Tarragony w świetle źródeł pisanych i archeologicznych - Zimnowodzka, Anna (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The origins of Roman Tarragona reach back to the 3rd century, when – in 218 BC – the Romans set up a military camp on the location of the Iberian oppidum of Kese/Cese. Its strategic layout was appreciated by the Roman commanders during the Punic Wars and throughout the conquest of Iberian Peninsula. In the 1st century BC, Tarragona became a Roman colony (colonia Iulia Urbs Triumphalis Tarraco) and in 27 BC – a province, which resulted in dynamic urban development. The prosperity of Tarraco reached its climax at the beginning of the 2nd century AD, when many important administrative and religious buildings, as well as places of public entertainment, such as a theatre, an amphitheater and a circus, were erected. The second half of the 2nd century brought a slowdown in urban development, both inside the city walls and behind them. In the 3rd century, just outside the walls, a large necropolis grew, which in 258 became a burial ground for the ashes of Bishop Fructuosus and his deacons, martyred in the local amphitheater. In the 4th century, a vast pilgrimage center arose around the martyrs’ tomb, attracting worshippers from all over the Christian world. The next century brought many changes in numerous aspects of the city. The monumental Roman edifices ceased to perform their civic and religious functions. Along with the increasing importance of the Christian faith and the cult of martyrs, churches and monasteries were erected one by one, first on the outskirts of the city and then, from the 6th century onwards, also inside the city walls.